Calculation Methods of Seepage Coefficient for Clay Based on the Permeation Mechanism. (3rd March 2019) - Zhang, Yu; Chen, Tielin; Zhang, Yujun; Ren, Weizhong
Abstract : The existing empirical methods of the seepage coefficient for clay have difficulty in parameter acquisition and are poor in calculation accuracy, and it is possible to find reasonable ones based on the mature empirical methods of coarse-grained soil. Firstly, the permeation mechanism of clay was analysed including influencing factors, spatial process, and parameter calculation, and the ineffective and effective voids were defined; then the empirical methods of clay and coarse-grained soil were summarised and listed. Secondly, clay was put equivalent to coarse-grained soil according to bound-water consolidation, and the parameter "equivalent void ratio" was introduced to establish the equivalent calculation methods. Finally, the liquid-plastic limit method determining the volume of ineffective voids was explained, and the feasibility of equivalent calculation methods was evaluated by three examples. The results show that seepage, permeation, and effective permeation are three different concepts; groundwater permeates in clay via the effective void. For certain soil, the increasing sequence of permeability coefficients is the seepage coefficient, permeation coefficient, and effective permeation coefficient. Introduction of the "equivalent void ratio" unifies the calculation of the seepage coefficient for clay and coarse-grained soil. The maximum of the bound-water content is about 0.9 time the size of liquid limit. The Mesri equation and the equivalent calculation method of Terzaghi or Curson–Karman are suitable for calculating the seepage coefficient of clay for the closest results to experimental values.